Barriers to care and treatment for patients with chronic viral hepatitis in Europe: a systematic review. (16th May 2014) - Papatheodoridis, George V.; Tsochatzis, Emmanuel; Hardtke, Svenja; Wedemeyer, Heiner
Abstract Background & Aims Despite the availability of effective therapies for hepatitis B (HBV) and C virus (HCV), only a minority of these patients receive treatment. We systematically reviewed published data on barriers to management for chronic HBV/HCV patients in Europe. Methods Literature search to identify studies including adult patients with chronic HBV/HCV infection from European countries and data on barriers to treatment. Results Twenty‐five studies including 6253 chronic HBV and 19 014 HCV patients were identified, of which only two were from Eastern Europe. The mean rate of no treatment in HBV patients was 42% being higher in North‐Western European countries than Italy (56% vs. 39%, P < 0.001). Immigrants represented the most common barrier to HBV treatment. The mean rate of no treatment in HCV RNA‐positive patients was 57%, being highest in Romania (89%), intermediate in France (79%) and lower though still high in other European countries (52%, P < 0.001). The predominant barriers to HCV treatment were lack of financial resources in Romania and direct/indirect limitations of interferon‐alfa and/or parenteral drug and alcohol abuse in other countries. The mean rate of no treatment was highest in HCV RNA‐positive parenteral drug users (72%) and intermediate in those with HCV–HIV co‐infection (64%). Conclusions A substantial proportion of diagnosed chronic HBV and the majority of diagnosed HCV patients remain untreated. The rates and most importantly the reasons of barriers to treatment in chronic HBV/HCV patients vary widely among European countries supporting the need for country‐specific national strategies, resource allocation and implementation of global management policies.